Persepsi Wisatawan Milenial Terhadap Ekowisata Situ Gede Kota Bogor - Sugih Setiawan, Aditya; Utami, Nisa Rahmaniyah (Prasetiya Mulya Publishing, 2022)
One of the ecotourism areas favored by the millennial generation in West Java is Situ Gede Ecotourism. The purpose of this study is to determine the perception of millennial tourists towards ecotourism in situ Gede in terms of 4 indicators, namely: Attractions (Attractions), Accessibility (Accessibility), Amenities (Amenities), and Ancillary Service (Tourism Support Services). The research method used is a quantitative approach. The sample in this study was 50 respondents. Analysis of the data used is descriptive analysis. The achievement of millennial tourists' perceptions of attraction is 75.6%. Meanwhile, the achievementmillennialnial tourists' perceptions of accessibility are 87.5%. The achievememillenniallenial tourists' perceptions of amenities (amenities) are 78.8%. Another case is the achievement of millennial tourists' perceptions of Ancillary services (Tourism Support Services) of 73.5%